Diet Patterns Featuring Western-Style and Low-Preparation Foods Differentially Relate to Cognitive Function in Early Childhood From the STRONG Kids 2 Birth Cohort Study - Arden L McMath; Shelby A Keye; Jennifer M Barton; Corinne N Cannavale; Samantha J Iwinski; Kelly F Bost; Sharon M Donovan; Naiman A Khan (Current Developments in Nutrition)
Background: Dietary intake in early life is implicated in cognitive development. Objectives: This study aimed to investigate how diet patterns derived at 2, 3 and 4 y old relate to executive functions and early cognitive and academic skills using data from the longitudinal STRONG Kids 2 cohort. Methods: The Behavioral Inventory of Executive Functions Preschool caregiver survey was used to assess executive functions in 2 and 4 y olds. A subsample of children completed a modified Eriksen flanker to measure attentional inhibition, a hearts and flowers switch task to assess cognitive flexibility, and the Woodcock Johnson Early Cognitive and Academic Development tests to assess academic abilities during preschool ages (between 4 and 6 y old). Block Food Frequency Questionnaire items were grouped into 23 food groups, and dietary patterns were derived using principal component and confirmatory factor analyses. Three diet patterns were derived at each age (2, 3, and 4 y old); children were not assigned to a specific diet pattern but, rather, had 3 different diet pattern scores that were used for analyses. Diet pattern scores were used as predictors of executive functions at 2 (n = 217) and 4 y old (n = 250–266), as well as attentional inhibition (n = 53–56) and cognitive flexibility (n = 50–59) tasks and cognitive (n = 65–71) and academic (n = 55–57) scores in preschooler subsample. Results: Diets with higher intake of processed meats, sweets, and fried foods at 3 y old was related to lower Woodcock Johnson scores (all β ≥ −0.351, false discovery rate–adjusted P value = 0.028), whereas those with higher intakes of grains, nuts/seeds, and condiments at 2 y was related to greater incongruent flanker accuracy (β: 0.380; ΔR2 = 0.132; false discovery rate–adjusted P value = 0.030). Diet patterns from 2 to 4 y old were related to academic achievement and attentional inhibition; however, these associations were not independent of diet pattern at time of cognitive assessments. Conclusions: This study emphasizes the potential value of exploring early diet interventions aimed at improving dietary patterns to support cognitive development.